Characterization and HDS performance of sulfided CoMoW catalysts supported on mesoporous Al-SBA-16 substrates. (1st June 2015) - Huirache-Acuña, R.; Zepeda, T.A.; Rivera-Muñoz, E.M.; Nava, R.; Loricera, C.V.; Pawelec, B.
Graphical abstract: Al incorporated into SBA-16 led to both Brønsted and Lewis acidity that is beneficial for HDS reaction. Highlights: CoMoW sulfide catalysts supported on mesoporous Al-SBA-16 silica are active in HDS of DBT. The CoMoW/SBA-16 catalyst modified with a largest amount of Al displayed the largest HDS activity. Al-incorporation on SBA-16 by direct synthesis method results in formation of Brønsted and Lewis acid sites. Bifunctionality of CoMoW/Al-SBA-16 catalysts improves their performance for HDS of DBT. Abstract: In this work, the catalytic activity of ternary Co–Mo–W/Al-SBA-16 systems was investigated in the reaction of hydrodesulfurization (HDS) of dibenzothiophene (DBT) performed in a batch reactor at 350 °C and total H2 pressure of 33.8 bar. The synthesized materials were characterized by a variety of techniques (chemical analysis, N2 adsorption–desorption isotherms, XRD, TPR, TPD-NH3, FTIR of adsorbed pyridine, DRS-UV–vis, HRTEM and XPS). By applying the direct synthesis method, high surface area substrates with Al 3+ incorporated into the silica framework. The activity results indicate that all CoMoW/Al-SBA-16 catalysts were active in the HDS of DBT, the largest activity was found in the catalyst with the highest Al-content. This behavior was explained in terms of its largest specific area and good dispersion of the metal sulfide phases having average size of 3.3 nm (from HRTEM). Moreover, FT-IR spectroscopic study of adsorbed pyridine indicated Al incorporation into a SBA-16 substrate produces both Brønsted and Lewis acidities, which are beneficial for the HDS of DBT. All catalysts showed a high selectivity towards biphenyl indicating that HDS of DBT reaction proceeds mainly via direct desulfurization (DDS) reaction pathway.